Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jafc.2c01950
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum Combined with Galactooligosaccharides Supplement: A Neuroprotective Regimen Against Neurodegeneration and Memory Impairment by Regulating Short-Chain Fatty Acids and the c-Jun N-Terminal Kinase Signaling Pathway in Mice

Abstract: Probiotics and prebiotics have received attention in alleviating neurodegenerative diseases. Lactobacillus plantarum (L. plantarum) 69-2 was combined with galactooligosaccharides (GOS) and supplemented in a D-galactose (D-gal)-induced neurodegeneration and memory impairment mice model to explore its effects on the brain and the regulation of short-chain fatty acids. The results showed that the L. plantarum-GOS supplementation inhibited D-gal-induced oxidative stress and increased the brain's nuclear factor ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
(88 reference statements)
0
21
0
Order By: Relevance
“…With the increase in storage temperature, the total bacterial count increased faster because low temperatures inhibited the growth activity of bacteria [ 33 ]. However, when the optimal growth temperature of bacteria is reached, the bacteria will multiply rapidly, thus affecting the quality of mayonnaise [ 34 , 35 ]. In addition, the total bacterial count of SOB-substituted mayonnaise was consistently lower than that of whole-egg mayonnaise during storage.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase in storage temperature, the total bacterial count increased faster because low temperatures inhibited the growth activity of bacteria [ 33 ]. However, when the optimal growth temperature of bacteria is reached, the bacteria will multiply rapidly, thus affecting the quality of mayonnaise [ 34 , 35 ]. In addition, the total bacterial count of SOB-substituted mayonnaise was consistently lower than that of whole-egg mayonnaise during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) derived from fermented foods are considered natural and safe [ 19 ]. Accordingly, the use of probiotics for the alleviation of neurodegenerative diseases, including depression, have gained attention in recent years [ 20 ]. The relative abundance of Lactobacillus was reported to be closely related to the serum level of 5-HTP [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of others showed that diets deficient or low in dietary fiber exacerbate colitis development, while greatly high intake of dietary fiber or the acetate protects against colitis ( 43 ). Butyrate was a major energy source for colonic epithelial cells, reduced intestinal mucosal permeability, promoted intestinal barrier restoration, and prevented or reduced the incidence of colon cancer ( 44 ), Butyrate may inhibit the growth of cancerous colonocytes, and energy homeostasis necessary for the rapid cell proliferation of the colonic epithelium ( 45 , 46 ), and propionate had positive effects on metabolic health, such as lowering serum cholesterol ( 47 ). The total content of SCFAs in both WE and WT were very high, which indicated that sweet and tartary buckwheat had completely significant effects on the intestinal health.…”
Section: Resultsmentioning
confidence: 99%